Efficacy of first-line chemotherapy combined with immunotherapy or anti-angiogenic therapy in advanced KRAS-mutant non-small cell lung cancer - Huiping Qiang; Yue Wang; Yao Zhang; Jingwen Li; Lincheng Zhang; Huawei Du; Xuxinyi Ling; Shuhui Cao; Yan Zhou; Runbo Zhong; Hua Zhong (Translational Oncology)
Background: Approximately 30 % non-small cell lung cancer (NSCLC) patients carry KRAS mutations in western countries. First-line chemotherapy combined with immunotherapy has been the standard therapeutic regimen for KRAS-mutant NSCLC patients. This population could also benefit from chemotherapy combined with anti-angiogenic therapy. However, few studies has reported on head-to-head efficacy comparisons between these two treatment strategies. Methods: We selected stage IV KRAS-mutated NSCLC patients diagnosed from 2017 to 2022. Their clinical baseline characteristics, first-line treatment strategy, whether combined TP53 or STK11 mutation, PD-L1 expression level, etc. were evaluated. The correlation between these factors and progression-free survival (PFS) and overall survival (OS) were analyzed. Results: A total of 273 patients received first-line systematic therapy. The most common mutation was KRAS G12C (34.3 %). First-line chemotherapy combined with immunotherapy brought significant survival benefits (mPFS: 11.0 months vs. 4.0 months, P = 0.0003; mOS: 17.0 months vs. 9.0 months, P = 0.0002) compared with first-line chemotherapy combined with anti-angiogenic therapy. Among the 203 patients who received first-line chemotherapy combined with immunotherapy, PD-L1 positive NSCLC patients responded better than PD-L1 negative patients (mPFS: 11.0 months vs. 4.0 months, P = 0.0004; mOS: 21.0 months vs. 11.0 months, P = 0.0005). ECOG PS score of 0–1 (HR=0.201, P = 0.001) and first-line chemotherapy combined with immunotherapy (HR=0.333, P = 0.009) were independent predictors of OS. Conclusions: Compared with first-line chemotherapy combined with anti-angiogenic therapy, first-line chemotherapy combined with immunotherapy has brought significant survival benefit to advanced KRAS mutant NSCLC patients, especially for PD-L1 positive patients.